Relational exploration. Combining description logics and formal concept analysis for knowledge specification - Rudolph, Sebastian (KIT Scientific Publishing, 2007)
This work introduces Relational Exploration, a method for acquiring complete relational knowledge about a domain of interest by successively consulting a domain expert without ever asking redundant questions. This is achieved by combining Description Logics (DL) and Formal Concept Analysis (FCA): DL formalisms are used for defining FCA attributes while FCA exploration techniques are deployed to obtain or refine DL knowledge specifications.